2014
DOI: 10.1002/eat.22330
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory treatment in anorexia nervosa: A review

Abstract: In severe cases of AN where the patient refuses life-saving treatment compulsory treatment needs to be considered. Future research should focus on the longer term effects of compulsory treatment and also on questions related to mental capacity in AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…85 Families are the main protective and enabling setting for children’s health, growth, and wellbeing. Economic development has generally brought changes in family structure, stability, and patterns of transition to the next generation of families.…”
Section: Enabling and Protective Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Families are the main protective and enabling setting for children’s health, growth, and wellbeing. Economic development has generally brought changes in family structure, stability, and patterns of transition to the next generation of families.…”
Section: Enabling and Protective Systemsmentioning
confidence: 99%
“…Together with declines in marriage, parental deaths from HIV in some countries, and parental migration for employment in others, there has been a global trend towards more single parent families. 85 Living with only one or neither parent is now common in much of sub-Saharan Africa and Latin America. 90,91 In Asia, the Middle East, sub-Saharan Africa, Central America, and South America, large numbers of adolescents now live with extended family members rather than parents.…”
Section: Enabling and Protective Systemsmentioning
confidence: 99%
“…The Pubmed search resulted in 192 titles for inspection and 7 abstracts for inspection of which 5 were not trials of treatment setting [28][29][30][31][32] and one was a review [33] and one new trial [34] was identified. The CCRCT Issue 6 of 12, June 2014 (n = 797723) search resulted in 20 titles for inspection of which two were duplicates and one new trial [29] was identified ( Figure 1).…”
Section: Results Of Searchmentioning
confidence: 99%
“…However, in order to reach that effect, they have more often resorted to nasogastric feeding, which can damage the psychological engagement with the patients (30,31).…”
Section: Discussionmentioning
confidence: 99%